QSPR Study on the Binding Constants of Coumarins and Human Serum Albumin - Li, Mei-Ping; Zhang, Sheng-Wan (Asian Journal of Chemistry, 2013)
Three-dimensional holographic vector of atomic interaction field (3D-HoVAIF) was used to describe the chemical structures of 20 coumarins and it was employed to the quantitative structure property relationship studies between the binding constants of coumarins and human serum albumin. Here the quantitative structure property relationship model was built by multiple linear regression and partial least square regression. The stability and prediction ability of the established model were strictly examined by leave-one-out cross-validation and external validation. Meanwhile, the model of built pointed out hydrophobic interaction is important especially the hydrophobic interaction between H atoms and sp3-hybridized O atoms (sp3O) is in favour of the binding constants. Furthermore, the satisfactory results showed that 3D-HoVAIF could preferably express the structure information of the coumarins.